The Effect of Spiritual Care Development to Reduce the Level of Depression in the Families of Intensive Care Patients - Nugroho Ari Wibowo; Diah Priyantini; Siswanto Agung Wijaya; Kristin Widiyowati; Nanik Dwi Lestari (Indonesian Journal of Global Health Research, 2025)
Depression is a mental condition that affects a person's physical, psychological and social functioning. Depression occurs when problems in life arise, such as feeling disappointed, lost, depression is also a form of feeling sad, which can cause unhappiness and hopelessness. This study aimed was to analyze the effect of spiritual care development to reduce the level of depression in the families of intensive care patients. This research design uses Quasy experiment pre and posttest. The population is all families of patients in the Intensive Care ward at RSUD Haji Surabaya, totaling 108 respondents. The sample size was 85 respondents who met the inclusion criteria. The independent variable from the research is spiritual care with the intervention medium being a spiritual kit and the dependent variable is the level of depression in the family who keeps the patient in the intensive care room. Data was collected using the Beck's Depression Inventory questionnaire and then analyzed using the Wilcoxon Signed rank test. The Z score value for the pre-post variable for the incidence of depression is -5.940 with a p value of Asymp. Sig. (2-tailed) of .000 < 0.05, it can be seen that there is a significant influence between the results of the level of depression before and after the spiritual therapy kit. Developing spiritual care using the spiritual kit method can reduce the level of depression in the families of intensive care patients.